Creation of a unique architectural structure of bioactive glass sub‐micron particles incorporated in a polycaprolactone/gelatin fibrous mat; characterization, bioactivity, and cellular evaluations. Issue 7 (23rd February 2019) - Fanaee, Sajjad; Labbaf, Sheyda; Enayati, Mohammad Hossein; Baharlou Houreh, Arezou; Esfahani, Mohammad‐Hossein Nasr
Abstract: In this study, submicron, monodispersed, spherical bioactive glass (BG) particles with a mean diameter of 720 ± 80 nm were produced through sol–gel process. The prepared BG particles were successfully incorporated into 70/30 (W/W) ratio of polycaprolactone/gelatin (PCL/GT) nanofibrous mats (250 ± 60 nm) through electrospinning to obtain a unique architectural structure for the first time. To enhance biodegradation and stability of the scaffolds, crosslinking using gluteraldehyde was applied. The structure, wettability, hydroxyapatite (HA) formation, cell adhesion, cell viability and osteogenic potential of the fibrous mats were evaluated. A continuous, uniform and hydrophilic structure of PCL/GT/BG was obtained. The fibers were found to be bioactive as they formed HA on their surface after immersion in simulated body fluid. The unique structure significantly reduced HA formation time to 5 days. For in vitro investigations, human dental pulp stem cells (hDPSCs) were cultured on PCL/GT and PCL/GT/BG fibrous mats. Results demonstrated good cell attachment after 4 and 24 h with no significant levels of cytotoxicity during 10 days of culture. Alizarin red staining was applied to quantitatively analyze the potential of PCL/GT/BG in osteogenic differentiation of hDPSCs. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2019.